Photodynamic impact of curcumin enhanced silver functionalized graphene nanocomposites on Candida virulence - Balakrishnan, Dhivyabharathi; Lee, Cheng-I (Discover nano, 2024)
Candida species are escalating resistance to conventional antifungal treatments, intensifying their virulence, and obstructing the effectiveness of antifungal medications. Addressing this challenge is essential for effectively managing Candida infections. The overarching objective is to advance the development of more efficient and precise therapies tailored to counter Candida infections. This study focuses on developing antifungal combined drugs using curcumin-enhanced silver-functionalized graphene nanocomposites (Cur-AgrGO) to effectively target key virulence factors of C. albicans , C. tropicalis , and C. glabrata ( Candida spp.). The green reduction of graphene oxide (GO) using bioentities and active molecules makes this approach cost-effective and environmentally friendly. The nanocomposites were characterized using various techniques. Combining Cur-AgrGO with photodynamic therapy (PDT) demonstrated effective antifungal and antibiofilm activity with delayed growth and metabolism. The nanocomposites effectively suppressed hyphal transition and reduced key virulence factors, including proteinases, phospholipases, ergosterol levels, and cell membrane integrity. The findings suggest that Cur-AgrGO + PDT has potential as a treatment option for Candida infections. This innovative approach holds promise for treating Candida infections. Graphical abstract